RISK ON INTERNATIONAL PUBLIC DEBT MARKETS IN YEARS 1970-1990 (Research Bulletins of the Faculty of Economic Sciences, 2021)
he aim of this article is to present the evolution of investment risk’s perception on public debt markets since 1970 until 1990. It was showed that using of foreign credits by national economies was risen after Bretton Woods system collapsed. However, this kind of debt was unsecured and it caused risk as an effect of financial condition of indebted countries as well as dynamic changes in global economic situation.The con-ducting research allows to prove that public debt created in 70. and 80. contained investment’s risk though it wasn’t easynoticeable. From this reason, hazardousness wasn’t analyzed until 1982. Despite the Mexico’s insolvency, the great change into attitude towards the risk on public debt markets happened only after 1986.
Keywords: risk, public debt market, solvency, crisis